Comparison of LABORAS with static incapacitance testing for assessing spontaneous pain behaviour in surgically-induced murine osteoarthritis - von Loga, IS; Miotla-Zarebska, J; Huang, Y-S; Williams, R; Jostins, L; Vincent, TL (Elsevier, 2020)
Objective Evoked responses following mechanical or thermal stimulation are typically used to assess pain behaviour in murine osteoarthritis (OA). However, there is no consensus on how best to measure spontaneous pain behaviour. Method OA by partial meniscectomy (PMX), or sham surgery was performed in 10-week old C57BL/6 male mice. Collagen-induced arthritis (CIA) was induced in 10 week old DBA1 male mice. Spontaneous pain behaviour, either at the time of active inflammatory disease (CIA), or over the 12 weeks after induction of OA, was assessed by static incapacitance testing (measuring percentage of weight placed through each hindlimb), and Laboratory Animal Behaviour Observation Registration and Analysis System (LABORAS) (translating cage vibrations of singly house animals into specific activities). Data were analysed by repeated measures two way ANOVA with post hoc testing comparing experimental groups with either sham operated or naïve controls. Results By incapacitance testing, two phases of painful behaviour were evident after PMX: a transient, post-operative phase, which resolved within one week, and a late OA pain phase starting 8 weeks post surgery and reaching statistical significance at week 12 (95% CI: sham 89.51–98.19, PMX 76.18–98.16). LABORAS, was able to detect pain behaviour in mice with CIA, but no statistically significant pain behaviour was observed in OA mice either post operatively (once analgesia had been controlled for) or at any later time points for any activity compared with the sham group. Conclusion Static incapacitance testing is superior to LABORAS for measuring spontaneous pain behaviour in surgically induced murine OA.